Legality Analysis of the Thousand (Gebu) Movement Program Towards Traders Receiving Productive Zakat Fund: BAZNAS Kabupaten Merangin 2022 - Wati, Ela Rahmah; Fauzi, Unang (Jurnal Hukum Ekonomi Syariah, 2022)
Knowing the legitimacy of the rules for the movement of a thousand for productive zakat beneficiaries and to find out whether there are sanctions or not for beneficiaries who do not obey to fill gebu tubes. The research method used in this research is descriptive qualitative. The types of data used are primary and secondary data. Data collection techniques in this study, namely interviews, observation, and literature study. The data analysis technique used is the inductive analysis method, because the data obtained is a description in the form of a description. The results of the research achieved are the legality of the existing rules in BAZNAS in the form of legal foundations in the form of laws, regional regulations, presidential instructions, Jambi Governor instructions and SOPs that have been set by BAZNAS Kabupaten Merangin and sanctions for zakat recipients who do not comply with filling gebu tubes have not been implemented in BAZNAS Kabupaten Merangin.